A Novel CAZAC Sequence Based Timing Synchronization Scheme for OFDM System - Anuja Das; Biswajit Mohanty; Benudhar Sahu (International Journal of Advances in Applied Sciences, 2018)
Several classical timing synchronization schemes have been proposed for the timing synchronization in OFDM systems based on the correlation between identical parts of OFDM symbol. These schemes   show poor performance due to the presence of plateau and significant side lobe. In this paper we present a timing synchronization schemes with timing metric based on a Constant Amplitude Zero Auto Correlation (CAZAC) sequence. The performance of the proposed timing synchronization scheme is better than the classical techniques